Galatheoid squat lobsters (Crustacea: Decapoda: Anomura) from the epipelagic bottom of the Indian Exclusive Economic Zone, with descriptions of five new species - Tiwari, Shivam; Padate, Vinay P.; Cubelio, Sherine Sonia; Osawa, Masayuki (Zootaxa, 2024)
Seven species of galatheoid crustaceans, including five new species, are reported from the southeastern Arabian Sea, southwestern Bay of Bengal, and western Andaman Sea, India, based on material collected from 56 to 113 m depths. Distinctions between the five new species (Galathea bharata sp. nov., G. kalingasagara sp. nov., G. quadrangularis sp. nov., Nanogalathea longispina sp. nov., and Sadayoshia brevirostrum sp. nov.) and their morphological close congeners are given in detail. The genus Nanogalathea Tirmizi & Javed, 1980 is rediagnosed to include N. longispina sp. nov. Trapezionida latior Baba, 2005 is recorded for the first time from Indian waters, indicating northward extension of its known geographical range. A specimen tentatively referred to Galathea aff. nasimae Karasawa, 2019 is also reported from the Andaman Sea.